2019
DOI: 10.1186/s13063-019-3740-6
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen in Duchenne muscular dystrophy (TAMDMD): study protocol for a multicenter, randomized, placebo-controlled, double-blind phase 3 trial

Abstract: BackgroundDuchenne muscular dystrophy (DMD) is an inherited neuromuscular disorder of childhood with a devastating disease course. Several targeted gene therapies and molecular approaches have been or are currently being tested in clinical trials; however, a causative therapy is still not available and best supportive care is limited to oral glucocorticoids with numerous long-term side effects. Tamoxifen is a selective estrogen receptor regulator, and shows antioxidant actions and regulatory roles in the calci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…In the past, a high dosage regimen of halofuginone, an anti-parasitic molecule used in veterinary medicine, combined with GCs led to the death of a DMD patient and abrogation of the clinical trial in 2016 [77]. One possible explanation could be found in the synergy between halofuginone and GCs [90][91][92][93]. When considering polypharmacy in DMD, exploring molecular interactions is of great importance in avoiding life-threatening drug combinations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, a high dosage regimen of halofuginone, an anti-parasitic molecule used in veterinary medicine, combined with GCs led to the death of a DMD patient and abrogation of the clinical trial in 2016 [77]. One possible explanation could be found in the synergy between halofuginone and GCs [90][91][92][93]. When considering polypharmacy in DMD, exploring molecular interactions is of great importance in avoiding life-threatening drug combinations.…”
Section: Discussionmentioning
confidence: 99%
“…When blocking an entire pathway, such as the TGF-β, TLR, JAK/STAT or the glucose metabolism pathway, many other functions in the cell will be affected with repercussions in the cellular activity, which can be noticed as side-effects in patients (Tables 1-8). Inhibition of the TGF-β pathway seems to often produce side-effects (Table 5) [85,[92][93][94][95]. Although some molecules have not yet been tested in clinical trials with DMD patients, such as losartan, suramin, and decorin, the potential side-effects make these molecules less attractive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamoxifen (TAM) is a selective estrogen receptor modulator that can either mimic or antagonize estrogens in a tissue-dependent manner ( Dorchies et al, 2013 ). TAM can elevate the level of pro-inflammatory cytokines and growth factors involved in muscle regeneration and fibrosis, such as TGF-β, insulin-like growth factor 1 (IGF1) and osteopontin ( Nagy et al, 2019 ). And then leads to an increased capacity of muscle-purified mitochondria to buffer cytosolic calcium ( Nagy et al, 2019 ).…”
Section: Therapeutic Strategies Targeting the Secondary Downstream Pathological Mechanismsmentioning
confidence: 99%
“…This suggests that denosumab merits further testing as an effective drug for the treatment of osteoporosis in patients with DMD. Tamixofen was evaluated for the treatment of DMD in a multicenter, randomized, placebo-controlled, double-blind phase 3 trial, which found that 20 mg tamoxifen daily for 48 weeks slowed the progression of ambulant and non-ambulant DMD ( 38 ). In another phase 3 trial, the DMD Long-term Idebenone Study (DELOS) trial, idebenone was shown to reduce the loss of peak expiratory flow and FVC in patients with DMD in comparison with placebo ( 39 ).…”
Section: Other Drug Treatments For Dmdmentioning
confidence: 99%